225 Rheumatic heart disease in Timor Leste school students (RHD-TL) follow-up study: assessment of secondary prophylaxis and outcomes in Timor Leste. (13th January 2020) - Horton, A; Remenyi, B; Davis, K; Mock, N; Paratz, E; Harries, J; Dos Santos, J A; Francis, J R
Abstract: Background: The Rheumatic Heart disease in Timor Leste school students (RHD-TL) study identified Timor Leste as having some of the highest rates of definite rheumatic heart disease (RHD) in the world. The RHD-TL follow-up study aimed to assess the delivery and outcomes of the secondary prophylaxis program in known patients with echocardiographic screen detected definite and borderline RHD. Methods: School-students in Timor Leste where reassessed over a 3-year period since the initial study in 2016. Prospective assessments included adherence to secondary prophylaxis, complications of prophylaxis, follow-up clinical assessment and serial echocardiography. Of the 48 patients, 25 Definite and 23 Borderline, 38 (79%) of all patients, and 92% of definite RHD cases have had one or more follow-up assessments including full datasets for adherence, recurrence rates and progression of disease. Follow-up is provided by the volunteer paediatric cardiology team and rheumatic heart disease team of two NGOs in collaboration with local clinics. Results: The median duration of follow-up of the 38 patients was of 1.6 years. The median age was 13 years (range 8-22) and 75% were female. Adherence rates in patients with definite RHD was on average greater than 95% during the follow-up period. Of the 23 patients with mild or moderate RHD one case with documented acute rheumatic fever (ARF) recurrence progressed whilst 8 cases improved on benzathine-penicillin G (BPG) therapy. There was no progression of the 6 borderline cases who were not prescribed BPG. Out of the 9 borderline cases in whom BPG was prescribed, one, with 67% adherence, had a documented episode of ARF leading to echocardiographic progression and moderate definite RHD. Conclusion: This was the first follow-up study to look at disease natural history, both in treated and untreated groups, in Timor-Leste and brought practical insights into the efficacy of the Timor Leste RHD monitoring and prophylaxis programs. Its ongoing project will enable advocacy and quality assessment for the program as it expands.